Effect of insulin on readmission for heart failure following a hospitalization for acute heart failure - Bertomeu‐Gonzalez, Vicente (ESC Heart Fail, 2020)
AIMS: Type 2 diabetes mellitus (T2DM) is common in patients with heart failure (HF) and is related with worse outcomes. Insulin treatment is associated with sodium and water retention, weight gain, and hypoglycaemia—all pathophysiological mechanisms related to HF decompensation. This study aimed to evaluate the association between insulin treatment and the risk of 1 year readmission for HF in patients discharged for acute HF. METHODS AND RESULTS: We prospectively included 2895 consecutive patients discharged after an episode of acute HF in a single tertiary hospital. Multivariable Cox regression, adapted for competing events, was used to assess the association between insulin treatment and 1 year readmission for HF in patients discharged after acute HF. Participants' mean age was 73.4 ± 11.2 years, 50.8% were women, 44.7% had T2DM [including 527 (18.2%) on insulin therapy], and 52.7% had preserved ejection fraction. At 1 year follow‐up, 518 (17.9%) patients had died and 693 (23.9%) were readmitted for HF. The crude risk of readmission for HF was higher in patients on insulin, with no differences in 1 year mortality. After multivariable adjustment, patients on insulin were at significantly higher risk of 1 year readmission for HF than patients with diabetes who were not on insulin (hazard ratio 1.28; 95% confidence interval 1.04–1.59, P = 0.022) and patients without diabetes (hazard ratio 1.26; 95% confidence interval 1.02–1.55, P = 0.035). CONCLUSION: Following acute HF, patients with T2DM on insulin therapy are at increased risk of readmission for HF. Further studies unravelling the mechanisms behind this association are warranted.